Nutritional status in relation to depressive symptoms among Chinese elderly in Malaysia - Choong, Horng Tatt; Adznam, Siti Nur'asyura; Ibrahim, Zuriati; Norazman, Camilla Wahida (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: The objective of the study was to determine the factors associated with depressive symptoms (DS) among Malaysian Chinese elderly. Methods: This was a cross-sectional study using interviewer-administered questionnaire conducted in a peri-urban area in Kajang, Selangor, Malaysia among 112 free-living residents aged 60 years and above, mean age 71.4±7.01 (60 to 89) years. Dietary food intakes and DS were assessed by 24-hour dietary recall and 15-items Chinese Geriatric Depression Scale (C-GDS-15), respectively. Anthropometric parameters were obtained using standard procedures. Results: The prevalence of DS among the respondents was 36.6%. Most respondents reported physically inactive (96.5%), abdominal obesity (61.6%) and on average high selenium (81.9 ± 54.44) and low calcium intake (309 ± 173.36). According to MLR model, folate (β=-0.206, p=0.007), magnesium (β=-0.209, p=0.007) and iron (β=-0.202, p=0.009) intake were significant predictors of GDS score only if they were analyzed separately in the MLR model. However, after adjustment for gender, and other dietary nutrient intake, there were only good money satisfaction (OR=2.48, p=0.001) and dietary intake of iron (OR=1.385, p=0.050) showed significant associations with lower risk reporting DS. Conclusions: Prevalence of DS could be restricted by achieving a good economic satisfaction for the living and adequate intake of dietary iron, which with good overall nutrient will reflect a good nutritional status and health being.